Images and contexts the historiography of science and modernity in India - Raina, Dhruv (Oxford University Press, 2003)
This work attempts to situate the historiography of science in India within a social theory of science. It deals with issues such as the paradigm shift within science studies, the move away from a west-centric theory of science, and future trends and possibilities
Includes bibliographical references and index
Keywords: Geschichte; Naturwissenschaft; Science / India / Historiography; Science / India / History; Science -- India -- Historiography; Science -- India -- History; Naturwissenschaften; Indien